Stress, perceived competence and guilt as predictors of depression in parents with chronic pain - Muñoz-Peña, Irene J.; González-Gutiérrez, José L.; Yunta-Rua, Laura; Pacho-Hernández, Juan C.; López-López, Almudena (Frontiers in Psychology, 2025)
Suffering from chronic pain (CP) and coping with parenthood can be challenging for parental mental health. Pain can hinder the ability to deal with demands related to parenthood, which can negatively affect their psychological well-being because of unmet caregiving expectations.Considering the limited amount of research regarding the mental health of parents with CP, the study's main aim was to test a predictive model based on previous scientific literature, using structural equation analysis, in which parental competence and parental guilt partially mediate the relationship between parental stress and depression. To examine the moderating role of CP, the model was tested on a group of parents with CP and a control group of parents without CP. The study included 380 parents from all over Spain, of which 200 formed the group with CP and 180 participants formed the control group. A cross-sectional design was used to collect data through self-report measures. Higher levels of stress, guilt, and depression were observed in parents with CP. Based on the results, both groups of parents showed a good fit with the predictive model; parental stress was a good predictor of symptoms of depression both in parents with and without CP, parental competence mediated the relationship between parental stress and depression, being the relationship between competence and depression partially mediated by parental guilt. This study is the first to quantitatively examine parental competence and guilt in parents with CP, and to analyze their role as mediators between parental stress and depression in both CP and healthy parents. The results confirm previous qualitative findings and extend them to parents with CP, showing that the tested model aligns with the main theories on stress, self-efficacy, and depression, as well as existing literature on CP. These results suggest the relevance of addressing parental stress levels for reducing and preventing depressive symptoms in parents with CP and the importance of working on guilt reduction and enhancing competence in order to improve the emotional well-being of parents. The need to take into account the mental health of parents with CP to improve their quality of life is discussed.